The impact of polarization‐maintaining and multimode fibre lengths on strain and temperature sensitivities of single‐mode–multimode–polarization‐maintaining–multimode–single‐mode‐based fibre optic sensors. Issue 5 (9th March 2021) - Wei, Jinpeng; Wu, Tianyin; Zhang, Fan; Shao, Laipeng; Lu, Hanglin; Hu, Junhui
Abstract: A fibre loop mirror sensor is proposed and demonstrated for strain and temperature measurements in experiment. In these schemes, fibre loop mirrors are constructed with single‐mode‐multimode‐polarization‐maintaining‐multimode‐single‐mode optical fibre (SMPMS) structures. The strain and temperature characteristics of the sensor, depending on the lengths of multimode fibre (MMF) and polarization‐maintaining fibre (PMF), are studied in the experiment. The results indicate that PMF and MMF lengths have less impact on strain sensitivity but a remarkable impact on temperature sensitivity, which is consistent with the theoretical analysis. The best strain and temperature sensitivities of an SMPMS structure sensor can reach up to 39.0 pm/με and 2.366 nm/°C, respectively. The sensors have the merits of easy fabrication, cost‐efficiency and high temperature sensitivity and are quite suitable for fields requiring high‐precision measurement.